Le débat juridique et religieux sur la sorcellerie en Libye - Mazek Ayoub (L’Année du Maghreb)
This article examines the criminalization of witchcraft in Libya, an act prohibited by Islamic law but long unregulated specifically by Libyan legislation. Until recently, witchcraft was treated as a fraud offense under Article 461 of the 1954 Penal Code. However, with the rise of the Salafi movement and its control over religious institutions in Libya, witchcraft has become a focal point of specific issues. The Salafi-oriented General Authority for Awqaf and Islamic Affairs, inspired by an earlier Saudi initiative, launched the “ḥaṣīn” program to combat witchcraft, accompanied by proposed laws aimed at criminalizing these practices with severe penalties, including the death penalty. In 2024, the Authority succeeded in enacting Law No. 6, which criminalizes witchcraft, conjuring, divination, and related practices. This law and the “ḥaṣīn” program have sparked intense debates. On one hand, they are criticized for infringing on fundamental freedoms such as freedom of conscience and the right to life. On the other hand, they are seen as an attempt to impose Salafi ideology, considered foreign to Libya by some. The article analyzes the context and motivations that led to the adoption of this law and its contents, notably through the legal and religious debate, while considering Libya’s political and social situation.